“Estudio de la cinética de secado de filetes de tilapia ( oreochromis sp.)” - Tello Panduro, Betty Elizabeth (2003)
The present work looks for to determine the drying conditions adapted by means of the study of the behavior of its kinetics, diffusivity and drying speed. lt was carried out in the laboratories of Engineering, Analysis of the Foods and Quality Control of the National University of San Martín. For the drying a dryer was used with automatic regulation of temperature and speed of air of drying vari~ble. Nine drying treatments were evaluated for fresh fillets without skin, to different combinations of temperature to 40, 50 and 60 ºC with speeds of air of drying of 0.5, 0.8 and 1.1 mis. During the process the behavior of the loss of water was observed by evaporation in function of the time of drying (Kinetics) until arriving to a humidity (b.h.) final of 8.5%. The difusividad of the present water was determined in the tilapia fillet adjusting the experimental values of drying kinetics to the equation of Fick for badge page, using the program MICROCAL ORIGIN 3.5, being a variation of the difusividad of 3.14 X 10 -9 up to 9.05 X 1 o -9 m2/s for temperatures between 40 and 60 ºC. Regarding the drying speed a constant, alone period of speed a falling period was not observed that it demonstrates that the drying speed for the tilapia fillets is governed by the difusividad. The treatment of better acceptance was determined by a sensorial analysis, where ten judges evaluated by means of an affective test (it climbs hedonic of five qualification points) the color, scent, texture and general appearance of the fillets of dehydrated tilapia. The result of this analysis gave a bigger acceptance for the treatment to temperature of 40 ºC, with speed of drying of 1.1 mis, for all the evaluated attributes. The isotherms of adsorption for the fillet of dehydrated tilapia were determined to temperatures of 40, 50 and 60 ºC using the method static gravimetric. The equation of GAB was the one that better it reproduced the experimental values, obtaining you values of coefficient of determination of 0.997, 0.996 and 0.998, for 40, 50 and 60 ºC, respectively. The analysis proximal for the fresh and dehydrated fillets, threw the following values: Humidity of 80.49%; proteins, 17 .38; lipids, 1.13% and ashy of 1 .0% for tresh fillet and 8.49%, 81.52%, 5.30% and 4.69% respectively for the fillets of dry tilapia.